The Effect of Interactive Power Point Learning Media Based on Local Wisdom on Dancing Skills in Elementary School Students - Angga Setiawan; Maria Ulfa Yudha Julistiyana (Universitas Islam Balitar, 2024)
This research is motivated by the problems faced by grade 2 students at SDN 1 Dongko, namely lack of understanding in detail about local wisdom, namely turonggo yakso dances starting from history, movements, as well as tools and materials used in performances, students are less motivated in participating in the learning process in dance subjects because the media used by teachers is still limited to the blackboard and extracurricular dance at school is still insufficient. While the problems experienced by teachers are that teachers are less focused in the learning process because teachers have busy obligations for performance reporting requested by the ministry, teachers also provide information related to facilities and infrastructure that support dance are also inadequate in the school and the school lacks teaching staff in the field of art, information from the results of interviews to hire a dance coach is also relatively expensive. The purpose of this study was to determine the effect of local wisdom-based interactive power point learning media on dance skills in elementary school students. the research method used is quantitative method with Quasi Experimental Design research design and the design used is Nonequivalent Control Group Design. The samples in this study were class 2A students as the experimental class and class 2B as the control class. The average score obtained from students' dance skills after being given treatment is 88.43, then the data is tested with a hypothesis acquisition of 0.002 <0.05, then Ha is accepted and H0 is rejected. Thus, it can be concluded that interactive power point learning media based on local wisdom has an effect on the dance skills of grade 2 students of SDN 1 Dongko.